Integrasi Konstruksi Ekologis Melalui Mind mapping dalam Pembelajaran Laporan Hasil Observasi bagi Siswa SMA - Fina Zaidatul Istiqomah; Shofiatun Baroroh; Ali Manshur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this study was to explore the effectiveness of the ecological-based mind mapping method in Observation Report (LHO) learning at the Tegaldlimo Favorite Senior High School (SMA) level. This study uses a qualitative research method with a case study approach. The subjects of the study were students of Tegaldlimo Favorite Senior High School. Data were collected through in-depth interviews with teachers and students, direct observation during the learning process, and document analysis. Data analysis techniques used thematic analysis techniques. The application of the mind mapping method, both manually and based on digital applications, increased literacy and better concept visualization, in Observation Report (LHO) learning at Tegaldlimo Favorite Senior High School has proven effective in improving students' literacy skills, especially in reading and writing texts. This method combines visual and textual elements, making it easier for students to understand and process complex material in depth, and to organize arguments logically. In addition, the mind mapping method increases students' creativity, memory, self-confidence, and active participation in discussions. Learning becomes more interactive, interesting, and relevant to the needs of the modern era. This approach not only improves learning outcomes, but also presents ecological innovations in learning that support students' literacy and digital skills